2016
DOI: 10.1080/14656566.2016.1197203
|View full text |Cite
|
Sign up to set email alerts
|

An update on the pharmacotherapeutic interventions for smoking cessation

Abstract: To improve chances of success, providers should consider patient preferences and prior experiences with quitting, provide medication-specific counseling for the selected therapy, and encourage adherence with the behavioral and pharmacotherapeutic treatment regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 65 publications
0
12
0
9
Order By: Relevance
“…Using vertebrate models, naltrexone has been demonstrated to reduce cocaine intake (Mello et al, 1990; Corrigall and Coen, 1991; Ramsey and van Ree, 1991) and seeking (Giuliano et al, 2013); opioid intake in animal models and humans (Negus and Banks, 2013), and has recently been shown to decrease cannabis self-administration and subjective effects in chronic cannabis users (Haney et al, 2015). Naltrexone has shown mixed effects on nicotine use in humans (Aboujaoude and Salame, 2016; Barboza et al, 2016; Kirshenbaum et al, 2016). Rodent studies indicate that naltrexone can reduce nicotine-induced locomotor sensitization (Goutier et al, 2016) self-administration at 2.0 mg/kg (Guy et al, 2014) but not 1.0 mg/kg or below (Le et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Using vertebrate models, naltrexone has been demonstrated to reduce cocaine intake (Mello et al, 1990; Corrigall and Coen, 1991; Ramsey and van Ree, 1991) and seeking (Giuliano et al, 2013); opioid intake in animal models and humans (Negus and Banks, 2013), and has recently been shown to decrease cannabis self-administration and subjective effects in chronic cannabis users (Haney et al, 2015). Naltrexone has shown mixed effects on nicotine use in humans (Aboujaoude and Salame, 2016; Barboza et al, 2016; Kirshenbaum et al, 2016). Rodent studies indicate that naltrexone can reduce nicotine-induced locomotor sensitization (Goutier et al, 2016) self-administration at 2.0 mg/kg (Guy et al, 2014) but not 1.0 mg/kg or below (Le et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that health-care professionals should seek to engage themselves in helping smokers quit, and should do so in a non-judgmental fashion, instead offering advice and support. This is particularly important when considering the effectiveness of anti-nicotine interventions and pharmacotherapy, which signi cantly increase the chance of successful smoking cessation [73][74][75]. In Poland, smokers can obtain anti-nicotine advice from general practitioners, but they have no access to smoking-cessation clinics, as no such institutions exist in many parts of the country [35].…”
Section: Discussionmentioning
confidence: 99%
“…Given that NRT was the first approved treatment for nicotine dependence, numerous studies and reviews have accumulated in the literature . Robust evidence suggests that NRT products are effective treatments for quitting smoking.…”
Section: Evidence‐based Treatmentsmentioning
confidence: 99%
“…4 Given that NRT was the first approved treatment for nicotine dependence, numerous studies and reviews have accumulated in the literature. 8,9 Robust evidence suggests that NRT products are effective treatments for quitting smoking. As such, it is not surprising that a systematic review including 150 trials, with over 50,000 participants, comparing any type of NRT versus placebo or non-NRT control group, reported that all NRT formulations consistently improved cessation rates.…”
Section: Nicotine Replacement Therapymentioning
confidence: 99%